Effect of the entomopathogenic fungus Beauveria bassiana on the control of ticks in cattle - Yari Briones, Danitza I. (2021)
This study was carried out to determine the effect of the entomopathogenic fungus Beauveria bassiana on the control of ticks in cattle. In total, 20 Fleckvieh female cattle were distributed in five treatments: T1 = control group, T2 = excipients (water + 0.6 ml of surfactant), T3 = 1.2x107 conidia (80 g of fungus + 0.2 ml surfactant), T4 = 2.4 x107 conidia (160 g of fungus + 0.4 ml of surfactant), T5 = 3.6x107 conidia (240 g of fungus + 0.6 ml of surfactant). The fungus was washed with water and surfactant to detach them from the substrate and then applied to the cattle by thick-drop spraying. The tick count was performed in six areas (neck table, groin, armpit) on days 0 (before treatment), 1, 2, 3, 5, 7, 9, 11 and 14. The significant decrease in the number of ticks were observed from day 7 on T3, T4, T5. The decrease in ticks on day 14 was 99% in T5, while in T3 and T4 it was 91 and 82%, respectively.